Efektifitas Relaksasi Napas Dalam Pada Pasien Hipertensi Dengan Gejala Nyeri Kepala Di Puskesmas Baki Sukoharjo - Mulyadi, Mulyadi, Supratman, SKM., M.Kes., Ph.D, Vinami Yulian, S.Kep., Ns., MSc (2016)
Normal blood pressure for adults is defined as a systolic pressure below 120 mmHg and a diastolic pressure below 80 mmHg. Abnormal blood pressure is higher than 120/80 mmHg. A systolic blood pressure of 140 mmHg or higher, or a diastolic blood pressure of 90 mmHg or higher is hypertension. Hypertension is classified as either primary hypertension or secondary hypertension. Headache is an important symptom of many organic body abnormalities and functional, headache is unpleasant sensations that involves emotion with or without tissue damage. Nonpharmacological therapy to reduce pain is a relaxation technique which consists of deep breathing in the chest and abdomen breathing with slow rhythmic frequency which has benefits as acute and chronic pain in a way do it constantly. The purpose of this study was to determine relaxation techniques effect of deep breathing to decrease headache intensity in patient with hypertension at health center of Baki Sukoharjo. This research method is Quasi Exsperiment pretest-posttest design approach Control Group Design by using two groups were divided into an experimental group and a control group. The population in this study were all patients with hypertension who have a headache, and samples in this study were 36 respondents were divided into two study groups. Data processing techniques using analytical techniques Wilcoxon test and Mann-Whitney Test. These results indicate that a pain scale of respondents in the experimental group showed a decrease in the segnifikan time before and after therapy relaxation deep breath, where the value Zhitung 3,357 and P = 0.001, or (P <0.05). While the control group was Zhitung 1,732 and P = 0.083, or (P> 0.05). The conclution is significant influence between deep breathing relaxation therapy to decrease headache intensity in patient with hypertension. Keywords : Hypertension, Headache, Deep Breathing Relaxation